Gambaran Hasil Pemeriksaan Monofilamen pada Pasien Diabetes Melitus (DM) yang Berkunjung ke Poliklinik Penyakit Dalam RSUD Arifin Achmad Provinsi Riau - Viona Ayu Safitri; Dani Rosdiana; Riezky Valentina Astari (Jurnal Ilmu Kedokteran, 2017)
Diabetes mellitus in increasing at an alarming rate and has become a global challenge. Diabetes mellitus type 2 is agroup of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin actionor both. One of the most complications of diabetes is diabetic neuropathy. Diabetic neuropathy refers to damage ofmotor nerves, sensory, and autonomic system. The aim of this study is to identify patients at risk for diabetic neuropathywith monofilament examination in internist polyclinic Arifin Achmad General Hospital from May to July 2017.Monofilament is an inexpensive, practical tool in everyday use and can be used in early detection of sensation loss inthe foot to prevent diabetic ulcer. This study is descriptive research with direct examination of patient diabetes type 2.There were 73 samples that fulfilled the inclusion criteria. Profile patients with diabetes in the polyclinic are female morethan male is 60,3%. The age group 56-65 years is the most age group of DM patients in the polyclinic is 52.1%.Duration of diabetes is 5-10 years (52.1%). The results of monofilament examination in patients with type 2 DM arescore 0-3 as many as 19 people (26%), score of 3.5-5 as many as 27 people (37%), and score> 5,5 as many as 27 people(37%).